Effectiveness of A structured teaching program on Leucorrhoea and it's management for women of Reproductive age group at selected college in Honavar - Verginia Dsouza; Chinchu C.J.; Manisha Kale; Anjali M.B.; Anjali Santhosh; Jesil Joy; Jismi Kuriakose; Nisha Molts; Poojamandal (International Journal of Women's Health Nursing And Practices, 2024)
Leucorrhea, also known as leucorrhea, is a white, yellow, or green discharge from a woman's vagina, which may be normal or asign of an infection. Leucorrhea is common during pregnancy and is typically normal if the discharge is thin, white, and odorless.Physiological leucorrhea is a condition that occurs in young women several months to a year after the onset of menstruation. It sometimes occurs in newborn girls and usually lasts for 2 to 3 months. In many instances, leukorrhea can indicate an infection, particularly if the discharge is yellow or green, has an unpleasant smell, and is accompanied by itching, burning sensations, or swelling of the tissue. This study evaluated the effectiveness of education regarding leukorrhea and its treatment in children ofchildbearing age. An experimental design consisting of pre-test, pre-test, and post-test was adopted with a sample size of 30 usinga non-random purposive sampling technique. Data was collected and evaluated through surveys that included 24 multiple-choice questions. T-tests were conducted to compare the mean scores before and after the test, and this relationship was further illustrated using the chi-square test. In the pre-test, the average knowledge score of the subjects was 10.56, the averagepercentage was 35.2% and the standard deviation was 2.76; In the post-test, the average knowledge score was 15.1, with apercentage of 50.3%, a standard deviation of 3.09% and a standard deviation of 15.1%. The t-test value is -4.05 (p<0.05), whichis smaller than the 0.05 value in the table and is highly significant. Therefore, the plan to use a white belt is valid and the findings(H1) are important. The chi-square test (χ2) showed that the relationship between children's age test scores and variables such aseducation, family type, genital area knowledge, and content was analyzed at the 0.05 significance level. This study concluded thatleukorrhea treatment plans and management education can increase women's knowledge. Similar studies can be repeated indifferent locations with longer samples to generalize and conduct comparative studies between cities and rural areas. Educational training should provide both current and supplementary information to update knowledge about vaginal urination and its management. This training can be delivered within the community using various audiovisual aids.
Keywords: Assess; effectiveness; leucorrhea; management; planned teaching program